Greenhouse gas emissions from refrigeration equipment in Malaysia - Saidur, R.; Sattar, M.A.; Masjuki, Haji Hassan; Jamaluddin, M.Y. (Energy and Environment, 2009)
This paper presents an analysis of the greenhouse gas (GHG) emissions from refrigeration equipment. The refrigeration equipments use refrigerants such as chlorofluorocarbons (CFCs) and hydrofluorocarbons HFCs, which are believed to contribute the ozone depletion and global warming. Refrigeration equipment thus contributes indirectly through emission due to electricity consumption and directly due to the emission of refrigerants. Greenhouse gas emissions resulting from the burning of fossil fuels are quantified and presented in this paper. The calculation was carried out based on emissions per unit electricity generated and the type of fuel used. The direct emission of refrigerant was calculated based on emission factor and according to the procedure of Environmental Protection Agency (EPA), USA. A study was conducted to evaluate the refrigerant losses to the atmosphere and the CO 2 emission from fossil fuels to generate power to run the refrigeration and air-conditioning systems. In this paper, total appliance annual energy consumption by refrigerator-freezer and air conditioner as well as emission has been estimated for a period of 19 years (1997-2015) using the survey data. Energy savings and emission reductions achievable by raising thermostat set point temperature have been calculated for a period of 10 (i.e. 2005-2015) years.